A frog in the bog - Wilson, Karma; Rankin, Joan (New York : Margaret K. McElderry Books, 2003)
A frog in the bog grows larger and larger as he eats more and more bugs, until he attracts the attention of an alligator who puts an end to his eating.
Keywords: Frogs -- Fiction; Insects -- Fiction; Alligators -- Fiction; Stories in rhyme